(untitled) (The Peerian Journal, 2022)
This article is a comprehensive teaching and learning tool for computer literacy, the use of information technology in the process of technological education, the acquisition of skills, the use of information resources, the creation of electronic textbooks, the effective use of computer-based teaching methods. . The e-textbook provides students with interactive methods, psychological and pedagogical, modern information technology, audio lessons and video animations.